CHANGES IN LIPID METABOLISM IN CHRONIC HEART FAILURE ON THE BACKGROUND OF OVERWEIGHT AND OBESITY DEPENDING ON THE FUNCTIONAL STATE OF THE KIDNEYS - Bidzilya, P. (World of Medicine and Biology, 2016)
Changes in lipid metabolism in chronic heart failure on the background of overweight and obesity depending on the functional state of the kidneys. It is established that the deepening of renal dysfunction is accompanied by higher rates of low-density lipoprotein cholesterol, low-density lipoprotein cholesterol / high-density lipoproteins cholesterol ratio, triglycerides and triglycerides / high density lipoproteins cholesterol ratio. Distributed frequency of increased low-density lipoprotein cholesterol and low-density lipoprotein cholesterol / high density lipoprotein cholesterol ratio.